Optimality conditions in terms of convexificators for a bilevel multiobjective optimization problem. (2nd August 2020) - Dempe, S.; Gadhi, N.; El idrissi, M.
ABSTRACT: In this paper, we are concerned with a multiobjective bilevel optimization problem P, where the lower-level problem is also a multiobjective optimization problem. Using the optimal-value reformulation, together with a scalarization technique, under a nonsmooth generalized Guignard constraint qualification, one gives necessary optimality conditions for the initial problem. As an application, one deduces optimality conditions for a scalar bilevel programming problem in terms of convexificators. An example is given to illustrate our findings.